Effects of Pre-Pregnancy Exercise on Anxiety Behaviors and Oxidative Stress Factors in Pregnant Mice - Torabi, Farnaz; Eslami, Zohreh; Mohammadi, Mohammad (Health Nexus, 2025)
The physical and psychological status of the mother and the environment she provides during pregnancy significantly influence fetal development and, subsequently, the health and adaptability of the child in the future. Therefore, the present study aimed to investigate the effect of pre-pregnancy swimming exercise on anxiety behaviors and oxidative stress factors in female mice during pregnancy. In this study, 26 NMRI mice, approximately 80-90 days old and weighing 25-35 grams, were selected. The female mice were randomly divided into two groups: 10 in the control group and 10 in the experimental group. The female mice in the experimental group underwent swimming exercise for 8 weeks before mating. The exercise method included two stages: an adaptation stage and a swimming exercise stage. During the adaptation period, to reduce stress caused by water, the animals were placed in shallow water (5 cm depth) for 10 minutes during the first week to adapt to the procedure. The swimming exercise consisted of three 10-minute swimming sessions with a 10-minute rest interval between each session per day. To evaluate anxiety behaviors, the open field test, dark/light box test, and elevated plus maze test were utilized. For assessing oxidative stress factors, the mice were anesthetized, and blood was collected from their hearts. The obtained data were analyzed using SPSS version 26 and one-way ANOVA. The results indicated that in the experimental group (swimming exercise), compared to the control group (no exercise), there was a significant reduction in anxiety behaviors, a significant increase in glutathione, and a significant decrease in malondialdehyde levels (p≤0.05). It appears that pre-pregnancy swimming exercise reduces anxiety behaviors, increases glutathione, and decreases malondialdehyde in pregnant female mice. Therefore, it is recommended that swimming exercise be performed before pregnancy to control pregnancy-related anxiety in female mice.